AIE-active dual-pore covalent organic framework for colorimetric/fluorescence detection and degradation of perfluorooctanoic acid - Tianyuan Yu; Shuai Liu; Shaoxi He; Guoyi Pu; Xi Zhang; Yanxiong Liu; Wenyu He; Ziyu Bao; Zezhou Zhao; Jiahui Liu; Fei Li; Rong Sheng Li; et al. (Chemical Engineering Journal, 2026)

Multi-copy expression of classical swine fever virus E2 in a recombinant pseudorabies virus enhances immunogenicity and supports its potential as a PRV-CSFV bivalent vaccine candidate - Xianfei Shang; Hui Zhao; Yufeng He; Zhenxiang Rong; Xiquan Ke; Jinglei Gao; Ke Zhang; Jiyuan Luo; Min Zhang; Huanchun Chen; Xiangmin Li; Ping Qian (Veterinary Microbiology, 2026)

PepOSX-AI: CPP - an interpretable transformer-based deep learning model for prediction of cell-penetrating peptides - Haowen Chen; Weiwei He; Kaiyan Feng; Rong Xu; Sheng Yin; Lin Zheng; Jing Chen; Mouming Zhao; Jucai Xu; Lijun You (Analytica Chimica Acta, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Phosphorus–boron synergistic carbonization/dormancy strategy enables polyurethane foams with aging enhanced fire safety - Shuang Li; Hai-Bo Zhao; Ming-Jun Chen; Lei He; Lin Zhang; Fu-Rong Zeng; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Study on the anti-inflammatory effects of active ingredients in Vespa velutina auraria Smith - Ming-Rong Li; Xiu-Qin Pang; Chao-He Liu; Wei Zhang; Heng Liu; Hai-Rong Zhao; Zhi-Bin Yang; Yan Wang; Yi-Hao Che; Huai Xiao (Natural Product Research, 2026)

Research on Simulation Optimization of ART Charging Strategies in Automated Container Terminals - Hongqi Huang; Rong Yang; Mengjie He; Nenad Zrnic; Ning Zhao; Xiangwei Liu (Journal of Marine Science and Engineering, 2026)
In automated container terminals, Autonomous Rail-guided Transporters (ARTs) are responsible for horizontal transportation tasks between quay cranes and yard blocks during unloading operations. Their charging strategies directly affect operational continuity, charging resource utilization, and road traffic load. To improve the consistency between the simulation environment and the actual terminal layout, this study constructs a DXF-based directed traffic network based on the CAD/DXF layout of Tianjin Port Second Container Terminal. A coupled discrete-event simulation model integrating ART operations, charging behavior, and traffic dynamics is developed using SimPy. The study further compares several charging strategies, including threshold charging, conventional opportunity charging, safe opportunity charging, interval charging, and Distance-Aware Interval Charging (DAIC). The results indicate that the conventional opportunity charging strategy suffers from battery depletion failures under continuous unloading task flows due to the absence of mandatory low-battery protection. After introducing a safety threshold, the safe opportunity charging strategy effectively eliminates the risk of battery depletion. Considering comprehensive performance indicators, including operational success rate, task completion time, charging travel distance, charging frequency, minimum State of Charge (SOC), and road congestion level, the 40%/70% interval charging strategy demonstrates strong overall robustness, while the 40%/80% interval charging strategy shows advantages in completion time and charging resource utilization. Both strategies can therefore be regarded as key candidate charging schemes for ART operations in Tianjin Port Second Container Terminal.

Cholesteryl ester accumulation as a biomarker for personalized selection of fertility-preserving therapies in endometrioid endometrial carcinoma - Yijiao He; Shenyi Yin; Wenying Zhao; Yanmin Wang; Danhua Shen; Yi Wang; Jing Geng; Xiaobo Zhang; Ying Yu; Juan Li; Yang He; Jiaxin Li; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Late-spring vertical profiles in atmospheric water vapor stable isotopes reveal westerlies moisture transport across the Himalaya into the Asian Water Towers - Jing Gao; Jingjing Yang; Gebanruo Chen; Yigang Liu; Xiaowei Niu; Aibin Zhao; Yilong Wang; Rong Cai; Zeqing He; Taihua Zhang; Tandong Yao (Science Bulletin, 2026)

Microcrystalline cellulose modified with ethylenediamine disuccinate via ring-opening grafting reaction: A novel and efficient biosorbent for heavy metal ions - Ziyi Wang; Wenqi Wang; Lang Zhao; Min He; Rong Li (Carbohydrate Polymers, 2026)

Molten NaOH-KOH assisted thermo-chemical detoxification of waste salt containing hazardous organics - Hongping He; Yong Cheng; Linhua Jiang; Youcai Zhao; Dongjie Niu; Xunchang Fei; Rong Zhang; Shijin Dai (Process Safety and Environmental Protection, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Sulfur-doped TiO₂ with enhanced photocatalytic CO₂ reduction performance toward CO - Die He; Hui Ping Zhao; Hua Peng Guo; Rong Chen; Qiong Liu (Journal of Environmental Chemical Engineering, 2026)

Effect of long-term cultivation on ground arthropod diversity and network stability in desert agricultural ecosystems - Yongzhen Wang; Yilin Feng; Jialong Ren; Zhibin He; Jiliang Liu; Wenzhi Zhao; Rong Yang (Plant and Soil, 2026)

5-Methoxyflavone inhibits the proliferation of lung adenocarcinoma cells through PI3K/AKT/GSK3β/β-catenin/Cyclin D1 signaling and attenuates chemoresistance and PD-L1 expression - Yan Zhao; Yiwen Cui; Rong Li; Mingyong Li; Zhiwei He; Yingying Hu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Juvenile-Onset Cerebrotendinous Xanthomatosis with Novel Compound Heterozygous CYP27A1 Mutations: Case Series and Literature Review - Kefang Du; Chunrong Wang; Linlin Wan; Zhao Chen; Hongyu Yuan; Qian Jiang; Xiao Dong; Daji Chen; Riwei Ouyang; Xiafei Long; Xiaokang Wu; Xinying Xiao; et al. (The Cerebellum, 2026)

Widespread incongruence in the phylogenomics of the ancient land plant lineage, Selaginellaceae (lycophytes) - Jing Zhao; Hong Yu; Carl J. Rothfels; Jian-Jun Yang; Shao-Li Fang; Zhao-Rong He; Li-Bing Zhang; Xin-Mao Zhou (Molecular Phylogenetics and Evolution, 2026)

Cerium isotopic compositions of deep-sea sediments: implications for geochemical behavior of rare earth elements in the pelagic seafloor - Ganglan Zhang; Jianghao Bai; Mingyu Zhao; Pengcong Wang; Yangtao Zhu; Jun Cao; Hao Wu; Rong Xu; Gaowen He; Gangjian Wei; Yinan Deng (Geochimica et Cosmochimica Acta, 2026)

Screening of Fecal Bacteroides Strains and Discovery of Bacteroides eggerthii S13-F8 with Protective Effects Against Chemotherapy-Induced Diarrhea - Yi Zhao; Zhengqun Dai; Yanmei Lang; Rui Li; Hongyu Zheng; Jiajia Mi; Xiu He; Jin Liu; Rong Xiang; Xueran Mei; Yang Liu; Yantang Wang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Effects of green manure mulching on the trophic structure of soil fauna in desert agricultural ecosystems of northwestern China - Yongzhen Wang; Zhibin He; Jiliang Liu; Yilin Feng; Jialong Ren; Wenzhi Zhao; Rong Yang (Applied Soil Ecology, 2026)

Emerging trends in anticoagulation therapy: a bibliometric analysis of DOACs and endogenous coagulation pathway inhibitors - Zhe Zhu; Rong Huang; Hongli He; Rong Zhao; Xirui Li; Fangyan He; Dan Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Electrochemical and photoelectrochemical CO2 reduction to hydrocarbons by a copper-based molecular catalyst - Zhibing Wen; Rong Zhang; Yong Zhu; Hua Gao; Ran Zhao; Zhi Chen; Siyao Wang; Shuanglin He; Ya-Qiong Zhang; Rong-Zhen Liao; Fei Li (Chemical Engineering Journal, 2025)

Haloxylon ammodendron plantations: enhancing multi-trophic arthropod diversity and soil multifunctionality in arid deserts - Jialong Ren; Yongzhen Wang; Xiaogan Zhou; Wenzhi Zhao; Zhibin He; Rong Yang; Weidong Xin; Wei Ren; Chengchen Pan; Jiliang Liu (Journal of Environmental Management, 2025)

GO-enhanced polyurethane phase change materials with triple dynamic bonds: Oxime-urethane, coordination and hydrogen bonds - Rong Huang; Fu Zhao; Yongsheng Li; Zhuoni Jiang; Fangfang He; Kai Zhang; Zhengguo Chen; Guansong He; Wenbin Yang (Chemical Engineering Journal, 2025)

Extending the Mutational Spectrum of SYNE1 Ataxia in Chinese Patients - Xin Huang; Zhao Chen; Qian Jiang; Panyan Liu; Yiqing Gong; Lijing Lei; Jia Chen; Chunrong Wang; Linlin Wan; Lang He; Linliu Peng; Rong Qiu; et al. (The Cerebellum, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Bridging the knowledge gap: From poly(butylene adipate-co-terephthalatebutylene) degradation to CO2-generating mineralization under the synergistic effect of bacteria and fungi - Yue Wang; Qi Liu; Chang-Hong Xie; Ruo-Tong Zhao; Qiu-Xiang Tang; Dong-Fei Han; Yi-Ning Xia; Ji-Xiao Cui; Chang-Rong Yan; Wen-Qing He (Journal of Hazardous Materials, 2025)

A novel multi-dimensional viscoelastic mitigation device: Shake table tests and numerical assessment of precast concrete sandwich wall panel structure - Jia-Xuan He; Zhao-Dong Xu; Zhong-Wei Hu; Lian-Yu Zhang; Qiang-Qiang Li; Yao-Rong Dong; Gabriele Milani (Engineering Structures, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

The application of nutrients in enhancing drought tolerance of secretohalophyte Atriplex canescens in the desert regions of Northwest China - Jian-jun Kang; Wen-zhi Zhao; Zhi-bin He; Bing Liu; Rong Yang; Hai Zhou; Dong-Mei Zhang (Plant and Soil, 2025)

ZDHHC13 Reduces the Risk of Ischemic Stroke by Regulating Metabolites - Zhen Wei; Chunshu Rong; Wei He; Xu Wang; Dexi Zhao (Journal of Molecular Neuroscience, 2025)

Recent advances in fluorescent aptamer-based sensors for food safety analysis - Ranran Hou; Liuqin He; Xin Ji; Xiaoxiao Rong; Yulong Yin; Xing Li; Yunxuan Weng; Xiaoying Zhao (Trends in Food Science & Technology, 2025)

Modulation of surface properties and emulsifying properties of gliadin particles by alkyl gallates: Effects of pH and alkyl chain length - Can Wu; Ziqing Zhao; Rong He; Xinyu Liu; Bing Cui; Yuying Hu; Bin Zhou (Food Research International, 2025)

Glymphatic Impairment Associated with Neurocognitive Dysfunction in Moyamoya Disease - Chaofan Zeng; Yuanren Zhai; Peicong Ge; Chenglong Liu; Xiaofan Yu; Wei Liu; Junsheng Li; Qiheng He; Xingju Liu; Xun Ye; Qian Zhang; Rong Wang; et al. (Translational Stroke Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Efficient uranium(VI) recovery from fluorinated wastewater via deferiprone ligand complexation - Juanlong Li; Yezi Hu; Zewen Shen; Huihui Jin; Rong He; Wenkun Zhu; Guixia Zhao; Zhuoyu Ji; Bin Ma; Xiangke Wang (Water Research, 2025)

Diagnosis method for AUV propeller entanglement based on stylistic diversity and physics-guided priors - Wenfeng Zhao; Ze Yu; Shenghui Rong; Bo He (Ocean Engineering, 2025)

Phylogenomics of Paragymnopteris (Cheilanthoideae, Pteridaceae): Insights from plastome, mitochondrial, and nuclear datasets - Jing Zhao; Zhen-Long Liang; Shao-Li Fang; Rong-Juan Li; Chuan-Jie Huang; Li-Bing Zhang; Tanner Robison; Zhang-Ming Zhu; Wen-Jing Cai; Hong Yu; Zhao-Rong He; Xin-Mao Zhou (Molecular Phylogenetics and Evolution, 2025)

DNA aptamer-crosslinked hydrogel sensor: Design, mechanism and application for food safety analysis - Xinning Wang; Liuqin He; Xiaoxiao Rong; Ling Liu; Yulong Yin; Xiaoying Zhao; Yunxuan Weng (Trends in Food Science & Technology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

A plant growth-promoting bacterium supports cadmium detoxification of rice by inducing phenylpropanoid and flavonoid biosynthesis - Yingjie Wu; Haiyang Zhao; Meijuan Xiao; Huimin Liu; Hua He; Lu Peng; Qi Tao; Xiaoyan Tang; Yanyan Zhang; Rong Huang; Bing Li; Changquan Wang (Journal of Hazardous Materials, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Partial organic substitution increases soil quality and crop yields but promotes global warming potential in a wheat-maize rotation system in China - Gong Wu; Hai-meng Huang; Bei-bei Jia; Lei-lei Hu; Chong-sheng Luan; Qi Wu; Xiao-yu Wang; Xiao-xiao Li; Zhao Che; Zhao-rong Dong; He Song (Soil and Tillage Research, 2024)

Mechanism of β-MnO2 particle for the peroxymonosulfate activation under electric field: the promoting effect of carbamazepine on Mn(III) and reactive oxygen species production - Shaochun Yuan; Shuquan He; Qingyu Wu; Tuo Wang; Mengyu Li; Rong Liu; Yao Chen; Chuanliang Zhao; Fei Liu; Zhen Liu (Process Safety and Environmental Protection, 2024)

Phylogenomic analyses of the pantropical Platycerium Desv. (Platycerioideae) reveal their complex evolution and historical biogeography - Jing Zhao; Chuan-Jie Huang; Li-Ju Jiang; Zhao-Rong He; Shuai Yang; Zhang-Ming Zhu; Liang Zhang; Hong Yu; Xin-Mao Zhou; Jia-Guan Wang (Molecular Phylogenetics and Evolution, 2024)

Deciphering the evolution and biogeography of ant-ferns Lecanopteris s.s - Li-Ju Jiang; Jing Zhao; Jia-Guan Wang; Sven Landrein; Ji-Pu Shi; Chuan-Jie Huang; Miao Luo; Xin-Mao Zhou; Hong-Bin Niu; Zhao-Rong He (Molecular Phylogenetics and Evolution, 2024)

Research advances in technologies and mechanisms to regulate vinegar flavor - Zhankai Zhang; Zhi-hong Zhang; Ronghai He; Guozhong Zhao; Yongjian Yu; Rong Zhang; Xianli Gao (Food Chemistry, 2024)

Multifunctional property of N,N-bis (carboxymethyl) glutamic acid modified biomass material: adsorption and degradation removals of cationic dyes in wastewater - Min He; Lang Zhao; Hongbin Hu; Lu Yao; Yinghuai Guo; Chunjiang Hou; Shaokun Gao; Rong Li (Environmental Research, 2024)

Facile construction of plasmonic Ag/Nb2O5 films and their photocatalytic activity against organic dye and nanoplastics - Te Hu; Liang Hao; Qian Zhao; Rong Jia; Sujun Guan; Yiqiang He; Yun Lu (Journal of Water Process Engineering, 2024)

Bibliometric study of the application of the chicken embryo chorioallantoic membrane model in cancer research: the top 100 most cited articles - Chang Song; Dan-Dan Xiong; Rong-Quan He; Xiang-Zhi Yong; Zhi-Guang Huang; Yi-Wu Dang; Gang Chen; Yu-Yan Pang; Chun-Yan Zhao; Ning Qu; Dan-Ming Wei (Journal of Comparative Pathology, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Organic substitution regime with optimized irrigation improves potato water and nitrogen use efficiency by regulating soil chemical properties rather than microflora structure - Xiya Wang; Binggeng Yang; Lingling Jiang; Shicheng Zhao; Mengjiao Liu; Xinpeng Xu; Rong Jiang; Jun Zhang; Yu Duan; Ping He; Wei Zhou (Field Crops Research, 2024)

Suitable habitat evaluation and ecological security pattern optimization for the ecological restoration of Giant Panda habitat based on nonstationary factors and MCR model - Hui He; Xiangke Yu; Hui Yu; Zhigang Ma; Yong Luo; Tao Liu; Ziwei Rong; Jinhong Xu; Dianpeng Chen; Pengshang Li; Fuxin Yuan; Yongtao Zhao (Ecological Modelling, 2024)

Biochar modulates intracellular electron transfer for nitrate reduction in denitrifying anaerobic methane oxidizing archaea - Pan-Long Lv; Chuan Jia; Chi-Hang Wei; He-Ping Zhao; Rong Chen (Bioresource Technology, 2024)

Mass cytometry revealed the circulating immune cell landscape across different Suzuki stages of Moyamoya disease - Chenglong Liu; Peicong Ge; Bojian Zhang; Liujia Chan; Yuheng Pang; Chuming Tao; Junsheng Li; Qiheng He; Wei Liu; Siqi Mou; Zhiyao Zheng; Zhikang Zhao; et al. (Immunologic Research, 2024)
Moyamoya disease (MMD) is a cerebrovascular disorder marked by progressive arterial narrowing, categorized into six stages known as Suzuki stages based on angiographic features. Growing evidence indicates a pivotal role of systemic immune and inflammatory responses in the initiation and advancement of MMD. This study employs high-dimensional mass cytometry to reveal the immunophenotypic characteristics of peripheral blood immune cells (PBMCs) at various Suzuki stages, offering insights into the progression of MMD. PBMC samples from eight patients with early-stage MMD (Suzuki stages II and III) and eight patients with later-stage MMD (Suzuki stages IV, V, and VI) were analyzed using high-dimensional mass cytometry to evaluate the frequency and phenotype of immune cell subtypes. We identified 15 cell clusters and found that the immunological features of early-stage MMD and later-stage MMD are composed of cluster variations. In this study, we confirmed that, compared to later-stage MMD, the early-stage MMD group exhibits an increase in non-classical monocytes. As the Suzuki stage level increases, the proportions of plasmacytoid DCs and monocyte-derived DCs decrease. Furthermore, T cells, monocytes, DCs, and PMN-MDSCs in the early-stage MMD group show activation of the canonical NF-κB signaling pathway. We summarized and compared the similarities and differences between early-stage MMD patients and later-stage MMD patients. There is a potential role of circulating immune dysfunction and inflammatory responses in the onset and development of MMD.

Surface water resource attenuation attribution and patterns in Hai River Basin - Qingming Wang; Yong Zhao; Hao Wang; Jiaqi Zhai; Yue Zhang; Fan He; Rong Liu; Mengyang Ma (Science China Earth Sciences, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Impacts of land use and climate change on runoff in the Shaying River Basin based on SWAT model - Jie Tao; Yang Cao; Rong Gan; Qiting Zuo; Qingli Zhao; Yinxing He (Limnology, 2024)

Response of soil microbial properties in the life cycle of potatoes to organic substitution regimes in North China - Xiya Wang; Shicheng Zhao; Xinpeng Xu; Mengjiao Liu; Rong Jiang; Jun Zhang; Yu Duan; Ping He; Wei Zhou (Soil and Tillage Research, 2024)

Efficient perchlorate reduction in microaerobic environment facilitated by partner methane oxidizers - Pan-Long Lv; Chuan Jia; Chi-Hang Wei; He-Ping Zhao; Rong Chen (Journal of Hazardous Materials, 2024)

Different crystalline manganese dioxide and biochar co-conditioning aerobic composting: Reduced ammonia volatilization and improved organic fertilizer quality - Weijiang He; Shaopeng Rong; Jixiang Wang; Yingjie Zhao; Yunyi Liang; Junxia Huang; Lin Meng; Yanfang Feng; Lihong Xue (Journal of Hazardous Materials, 2024)

Partial organic substitution for synthetic fertilizer improves soil fertility and crop yields while mitigating N2O emissions in wheat-maize rotation system - Gong Wu; Shuo Yang; Chong-sheng Luan; Qi Wu; Lei-li Lin; Xiao-xiao Li; Zhao Che; De-bao Zhou; Zhao-rong Dong; He Song (European Journal of Agronomy, 2024)

Developing a highly efficient, environmentally friendly and cost-effective copper sulfide semiconductor sponge for nuclear wastewater treatment under one sun - Wencai Bai; Mengjiao Liu; Kaifu Yu; Xin Cao; Jie Lian; Zhibin Zhao; Yong Xiang; Baoliang Xu; Tao Chen; Rong He; Nan Sun; Wenkun Zhu (Journal of Environmental Chemical Engineering, 2024)

Microbial stratification protects denitrifying anaerobic methane oxidation archaea and bacteria from external oxygen shock in membrane biofilm reactor - Pan-Long Lv; Chuan Jia; Xu Guo; He-Ping Zhao; Rong Chen (Bioresource Technology, 2024)

A co-located QTL for seven spike architecture-related traits shows promising breeding use potential in common wheat (Triticum aestivum L.) - Jieguang Zhou; Qian Liu; Rong Tian; Huangxin Chen; Jian Wang; Yaoyao Yang; Conghao Zhao; Yanlin Liu; Huaping Tang; Mei Deng; Qiang Xu; Qiantao Jiang; et al. (Theoretical and Applied Genetics, 2024)

Soil pH differently affects N2O emissions from soils amended with chemical fertilizer and manure by modifying nitrification and denitrification in wheat-maize rotation system - Gong Wu; Fei Liang; Qi Wu; Xiao-Gang Feng; Wen-ding Shang; Hua-wei Li; Xiao-xiao Li; Zhao Che; Zhao-rong Dong; He Song (Biology and Fertility of Soils, 2024)

B4C/Ce co-modified Ti/PbO2 dimensionally stable anode: Facile one-step electrodeposition preparation and highly efficient electrocatalytic degradation of tetracycline - Zeyi Wang; Rong Su; Maojie Zhao; Luyao Zhang; Lu Yang; Feng Xiao; Weishan Tang; Lichuan Chen; Ping He; Dingming Yang (Chemosphere, 2023)

A novel active packaging film containing citronella oil: Preparation, characterization, antimicrobial activity and application in grape preservation - Weijie Zhao; Changcheng Li; Weijia Ma; Ruiwen He; Yan Rong; Shovra Sarker; Qi Liu; Fang Tian (Food Packaging and Shelf Life, 2023)

Membrane fabrication and configuration design development of photothermal membrane distillation (PMD) - Guo-Rong Xu; Min Wang; Ke Xu; He-Li Zhao; Qian Liu (Desalination, 2023)

Efficient capture of iodine by charge-induced effect of nitrogen-rich ionic liquids - Shi-Jie Guo; Guo-Hao Zhang; Qiu-Hong Zhu; Chao Yu; Jia-Ying Liu; Xiao-Lan Yang; Song Qin; Nan-Rong Zhao; Ling He; Guo-Hong Tao (Chemical Engineering Journal, 2023)

Bacillus amyloliquefaciens Induces Resistance in Tobacco Against Powdery Mildew Pathogen Erysiphe cichoracearum - Rong Jiao; Ayesha Ahmed; Pengfei He; Shahzad Munir; Yixin Wu; Junwei Wang; Pengbo He; Ge Wang; Huanwen Yang; Jing Zhao; Canhua Lu; Yongzhan Cai; et al. (Journal of Plant Growth Regulation, 2023)

P24-42: A new generation of fully human anti-CTLA-4 heavy chain-only, Porustobart, shows superior safety in nonclinical study and clinical trials - J. Rong; L. Ding; F. Chen; J. Zhao; Y. He; Y. Rong; V. Chen (Toxicology Letters, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

A GC/C/IRMS-based method for position-specific carbon isotopic analysis of saturated long chain fatty acids - Yu Zhao; Ran Ma; Yaoting Qi; Rong He; Zhenyu Zhu; Bo Wang; Ying Wang; Qiulin Yan; Maxime Julien; Youping Zhou (Organic Geochemistry, 2023)

One-step electrodeposition preparation of boron nitride and samarium co-modified Ti/PbO2 anode with ultra-long lifetime: highly efficient degradation of lincomycin wastewater - Maojie Zhao; Mengqi Yang; Peilin Yang; Rong Su; Feng Xiao; Ping He; Hongquan Deng; Tinghong Zhang; Bin Jia (Environmental Science and Pollution Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Strong and continuous MXene/sodium alginate composite fibers prepared by immersion rotary jet spinning process with outstanding electromagnetic interference shielding performance - Guoxin Zhao; Chao Sui; Linlin Miao; Junjiao Li; Lei Wen; Gong Cheng; Chenxi Zhao; Weizhe Hao; Yuna Sang; Jiaxuan Li; Zhuochao Zhang; Yushun Zhao; et al. (Chemical Engineering Journal, 2023)

A 3D phytic acid cross-linked high-porous conductive hydrogel integrating g-C3N4 for electrochemical multiplex sensing of heavy metal ions - Lu Xiao; Yulan Zhao; Gang Chang; Huiling Yan; Rong Zou; Xiuhua Zhang; Shengfu Wang; Hanping He (Analytica Chimica Acta, 2023)

High-resolution forest age mapping based on forest height maps derived from GEDI and ICESat-2 space-borne lidar data - Xudong Lin; Rong Shang; Jing M. Chen; Guoshuai Zhao; Xiaoping Zhang; Yiping Huang; Guirui Yu; Nianpeng He; Li Xu; Wenzhe Jiao (Agricultural and Forest Meteorology, 2023)

Coaxial electrospun nanofibrous substrates with tunable wettability for constructing cucurbit[n]uril-embedded organic solvent nanofiltration membranes - Qian Wang; Qin-Yuan He; Liu-Lin Zhao; Yue Wang; Rong Fang; Cong Luo; Wei-Tong Lu; Hong-Ya Jiang; Shi-Peng Sun; Xue-Li Cao (Chemical Engineering Journal, 2023)

Grass harvesting eliminates the beneficial effects of legume addition on soil nematode communities in a tall grass pasture - Jie Zhao; Wei Zhang; Xin Liu; Rong Yang; Dan Xiao; Xunyang He; Kelin Wang (Agriculture, Ecosystems & Environment, 2023)

Corrigendum to “Promotional effects of calcination temperature and H2O on the catalytic activity of Al-substituted MnAlO catalysts for low-temperature acetone oxidation” [Chemosphere 301 (2022) 134722] - Wan-Peng Zhang; Kun Wu; Junyi Zhao; Jun He; Leiping Wang; Hang Xiao; Jian-Bing Guo; Jian-Rong Li (Chemosphere, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Zinc efficiently extracted from zinc calcine by reduced wet grinding: ZnFe2O4 to ZnO and Fe3O4 - Shaoqin Chen; Xiangfei Zeng; Qian Liang; Ling Hu; Shuyuan Chen; Dejun He; Yunhui Han; Zhisheng Zhao; Rong Huang; Yin Huang; Songshan Zhou; Jiqin Wang; et al. (Journal of Cleaner Production, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Shaking table tests and seismic assessment of a full-scale precast concrete sandwich wall panel structure with bolt connections - Jia-Xuan He; Zhao-Dong Xu; Lian-Yu Zhang; Zhi-Hua Lin; Zhong-Wei Hu; Qiang-Qiang Li; Yao-Rong Dong (Engineering Structures, 2023)

Exposure–response relationship between temperature, relative humidity, and varicella: a multicity study in South China - Yihan Li; Jialing Li; Zhihua Zhu; Weilin Zeng; Qi Zhu; Zuhua Rong; Jianxiong Hu; Xing Li; Guanhao He; Jianguo Zhao; Lihua Yin; Yi Quan; et al. (Environmental Science and Pollution Research, 2023)

Analysis of the effect of seasonal changes on sensitive parameters of LAI-based Penman–Monteith evapotranspiration model based on particle swarm algorithm - Hao Duan; Xin He; Hongli Zhao; Xiaohui Jin; Haowei Xu; Rong Wang (Acta Geophysica, 2022)

MicroRNA alteration in cerebrospinal fluid from comatose patients with traumatic brain injury after right median nerve stimulation - Ying Jia; Yi-fan He; Ye Tian; Yuan-zhi Wang; Rui-ting Zhao; Xiao-chun Li; Jian Sun; Ying-sheng Wei; Shuo An; Heng-jie Yuan; Chun-xiao Wan; Rong-cai Jiang (Experimental Brain Research, 2022)

Analysis of Grain Yield Formation Components of Extra Heavy-Panicle-Type Mid-Season Indica Hybrid Rice - Xiaolong Zhong; Hafiz Athar Hussain; Bingbing Zhao; Manyu Huang; Saddam Hussain; Rong Xie; Linjun Cai; Han Yun; Guanghua He; Changwei Zhang (Journal of Plant Growth Regulation, 2022)

Effects of Dietary Rhodobacter sphaeroides Protein Substitution of Fishmeal and Coenzyme Q10 Supplementation on Growth Performance, Intestinal Microbiota and Stress Tolerance of Litopenaeus vannamei in Acute Low Salinity - Zhihong Liao; Yangyang Gong; Ziqiao Wang; Yingjie Wang; Rong Yao; Mengdie Chen; Dan Wei; Wei Zhao; Xuanshu He; Jin Niu (Frontiers in Marine Science, 2022)
A 56-day culture experiment followed by an acute low salinity challenge was conducted to evaluate the effects of Rhodobacter sphaeroides protein (RSP) substitution of fishmeal and Coenzyme Q10 (CoQ10) supplementation on growth performance, intestinal microbiota and compressive capacity of Litopenaeus vannamei ( L. vanname i). Four experimental diets were formulated: FM diet (20% fishmeal), RSP diet (20% RSP instead of 20% fishmeal), CoQ10 diet (20% fishmeal supplemented with CoQ10 at 0.08 g kg –1 ), RSP + CoQ10 diet (20% RSP supplemented with CoQ10 at 0.08 g kg –1 ). The obtained results were denoted that L. vannamei fed CoQ10 diet could improve growth performance (weigh gain and specific growth rate), condition factor and crude lipid, and decrease hepatosomatic index, but no differences were found in survival rates. High throughput sequencing on intestinal microbiota indicated that intestinal microbiota of L. vannamei consisted mainly of Proteobacteria and Firmicutes . The species richness of the RSP diet was remarkably higher than that of the other diets. Moreover, the presence of RSP and CoQ10 may improve intestinal homeostasis by inhibiting the propagation of Vibrio . Compared to FM diet and RSP diet, supplementation of CoQ10 significantly improved the compressive capacity of L. vannamei against the acute low salinity challenge, as indicated by higher survival rates as well as higher activities of T-AOC and higher transcript levels of SOD , HSP70 , and Relish gene. Our findings demonstrated that RSP could serve as a novel FM and CoQ10 could serve as a prospective feed additive to help L. vannamei to overcome environmental stresses.

Circ_0002711 knockdown suppresses cell growth and aerobic glycolysis by modulating miR-1244/ROCK1 axis in ovarian cancer - Weiquan Xie; Lu Liu; Chuanyong He; Min Zhao; Rong Ni; Zixiong Zhang; Chengyu Shui (Journal of Biosciences, 2021)

Activation of the Hippocampal LXRβ Improves Sleep-Deprived Cognitive Impairment by Inhibiting Neuroinflammation - Chen Qiu; Min Wang; Wen Yu; Zheng Rong; He-Sheng Zheng; Ting Sun; Shui-Bing Liu; Ming-Gao Zhao; Yu-Mei Wu (Molecular Neurobiology, 2021)

Effects of Mn2+ on neutral lipid content, C4 pathway, and related gene expression in Phaeodactylum tricornutum - Rong-Shi Chen; Li Zhang; Feng-Juan Wei; Lan-Ying Yuan; Pu Zhao; He-Yu Wang; Yi-Fu Gong (Journal of Applied Phycology, 2021)

Genotypic variation in nitrogen utilization efficiency in oilseed rape is related to the coordination of leaf senescence and root N uptake during reproductive stage - Huiying He; Yuyu Xie; Anyu Zhao; Wencong Hu; Xiao Guo; Anthony J. Miller; Xiaoming Wu; Biyun Chen; Rong Zhang; Hui Tian; Yajun Gao (Plant and Soil, 2021)

Transcutaneous Auricular Vagus Nerve Stimulation: From Concept to Application - Yu Wang; Shao-Yuan Li; Dan Wang; Mo-Zheng Wu; Jia-Kai He; Jin-Ling Zhang; Bin Zhao; Li-Wei Hou; Jun-Ying Wang; Lei Wang; Yi-Fei Wang; Yue Zhang; et al. (Neuroscience Bulletin, 2021)

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Discovery of new small-molecule cyclin-dependent kinase 6 inhibitors through computational approaches - Xiaojiao Luo; Yu Zhao; Pan Tang; Xingkai Du; Feng Li; Qingying Wang; Rong Li; Jun He (Molecular Diversity, 2021)

CuO Nanoparticle Exposure Impairs the Root Tip Cell Walls of Arabidopsis thaliana Seedlings - Guangli Nie; Jian Zhao; Rong He; Yulin Tang (Water, Air, & Soil Pollution, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Evidence of compliance with and effectiveness of guidelines for noninvasive prenatal testing in China: a retrospective study of 189,809 cases - Chan Tian; Tao Deng; Xiuhuang Zhu; Chen Gong; Yangyu Zhao; Yuan Wei; Rong Li; Xiufeng Xu; Miaonan He; Zhiwei Zhang; Jing Cheng; Mol BenWillem; et al. (Science China Life Sciences, 2020)

Two new benzophenones from endohydric moss Polytrichum Commune - Xu-Hong Duan; Jian-Cheng Zhao; Lin Li; Lin Pei; Pei He; Rong Wang (Natural Product Research, 2019)

Ecological Risk Assessment of Neodymium and Yttrium on Rare Earth Element Mine Sites in Ganzhou, China - Chun-Mei Zhao; Xing Shi; Si-Qi Xie; Wen-Shen Liu; Er-Kai He; Ye-Tao Tang; Rong-Liang Qiu (Bulletin of Environmental Contamination and Toxicology, 2019)

Evaluating giant panda as a surrogate species for conservation co-occurring species in the Baishuijiang National Nature Reserve - Zhanlei Rong; Xingming Liu; Chuanyan Zhao; Liwen He; Junjie Liu; Yunfei Gao; Fei Zang; Haojie Xu; Zhaoxia Guo; Yahua Mao (Environmental Science and Pollution Research, 2019)

Comparative proteomic analysis of Nostoc flagelliforme reveals the difference in adaptive mechanism in response to different ultraviolet-B radiation treatments - Shi-gang Shen; Rong-jun Guo; Rong-rong Yan; Yi-kai Wu; Dong-xue Zhao; Ya-hui Lin; He-xin Lv; Shi-ru Jia; Pei-pei Han (Molecular Biology Reports, 2018)

Frond transformation system mediated by Agrobacterium tumefaciens for Lemna minor - Gui-Li Yang; Yang Fang; Ya-Liang Xu; Li Tan; Qi Li; Yang Liu; Fan Lai; Yan-Ling Jin; An-Ping Du; Kai-Ze He; Xin-Rong Ma; Hai Zhao (Plant Molecular Biology, 2018)

UPregulated single-stranded DNA-binding protein 1 induces cell chemoresistance to cisplatin in lung cancer cell lines - Xiang Zhao; Rong He; Yu Liu; Yongkai Wu; Leitao Kang (Molecular and Cellular Biochemistry, 2017)

The dynamics of landscape-scale ecological connectivity based on least-cost model in Dongshan Island, China - Li-yun Wu; Dong-jin He; Wei-bin You; Zhi-rong Ji; Yong Tan; Li-li Zhao (Journal of Mountain Science, 2017)

Three-Dimensional Tricuspid Annular Motion Analysis from Cardiac Magnetic Resonance Feature-Tracking - Shuang Leng; Meng Jiang; Xiao-Dan Zhao; John Carson Allen; Ghassan S. Kassab; Rong-Zhen Ouyang; Ju-Le Tan; Ben He; Ru-San Tan; Liang Zhong (Annals of Biomedical Engineering, 2016)

Erratum to: An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Spy1 participates in the proliferation and apoptosis of epithelial ovarian cancer - Shumin Lu; Rong Liu; Min Su; Yingze Wei; Shuyun Yang; Song He; Xia Wang; Fulin Qiang; Chen Chen; Shuyang Zhao; Weiwei Zhang; Pan Xu; et al. (Journal of Molecular Histology, 2016)

An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2015)
IRF-1, a kind of transcription factor, is expressed in many cell types, except in early embryonal cells. IRF-1 has played an essential role in various physiological and pathological processes, including tumor immune surveillance, viral infection, development of immunity system and pro-inflammatory injury. However, the expression and function of IRF-1 in spinal cord injury (SCI) are still unknown. In this study, we have performed an acute SCI model in adult rats and investigated the dynamic changes of IRF-1 expression in the spinal cord. Western blot have shown that IRF-1 protein levels gradually increased, reaching a peak at day 3 and then gradually declined to a normal level at day 14 after SCI. Double immunofluorescence staining showed that IRF-1 immunoreactivity was found in neurons, but not in astrocytes and microglia. Additionally, colocalization of IRF-1/active caspase-3 was detected in neurons. In vitro, IRF-1 depletion, by short interfering RNA, obviously decreases neuronal apoptosis. In conclusion, this is the first description of IRF-1 expression in spinal cord injury. Our results suggested that IRF-1 might play crucial roles in CNS pathophysiology after SCI.

New cytotoxic and anti-inflammatory compounds isolated from Morus alba L. - Jing Qin; Min Fan; Juan He; Xing-De Wu; Li-Yan Peng; Jia Su; Xiao Cheng; Yan Li; Ling-Mei Kong; Rong-Tao Li; Qin-Shi Zhao (Natural Product Research, 2015)

Isolation from Proteus mirabilis of a novel class I 5-enopyruvylshikimate-3-phosphate synthase with glyphosate tolerance in transgenic Arabidopsis thaliana - Yong-Sheng Tian; Xiao-Fen Jin; Jing Xu; Jing Han; Wei Zhao; Xiao-Yan Fu; Ri-He Peng; Rong-Tan Wang; Quan-Hong Yao (Acta Physiologiae Plantarum, 2014)

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

Gene cloning and functional analysis of yellow green leaf3 (ygl3) gene during the whole-plant growth stage in rice - Xiaoqing Tian; Yinghua Ling; Likui Fang; Peng Du; Xianchun Sang; Fangming Zhao; Yunfeng Li; Rong Xie; Guanghua He (Genes & Genomics, 2013)

Erratum to: Olfactory responses of Neoseiulus cucumeris (Acari: Phytoseiidae) to odors of host plants and Frankliniella occidentalis (Thysanoptera: Thripidae)–plant complexes - Feng Zhong; Yu-Rong He; Yan Gao; Guo-Jun Qi; Chen-Yin Zhao; Li-Hua Lu (Arthropod-Plant Interactions, 2011)

Olfactory responses of Neoseiulus cucumeris (Acari: Phytoseiidae) to odors of host plants and Frankliniella occidentalis (Thysanoptera: Thripidae)–plant complexes - Feng Zhong; Yu-Rong He; Yan Gao; Guo-Jun Qi; Chen-Yin Zhao; Li-Hua Lu (Arthropod-Plant Interactions, 2011)

Quantitative estimation of the shrub canopy LAI from atmosphere-corrected HJ-1 CCD data in Mu Us Sandland - Wei Chen; ChunXiang Cao; QiSheng He; HuaDong Guo; Hao Zhang; RenQiang Li; Sheng Zheng; Min Xu; MengXu Gao; Jian Zhao; Sha Li; XiLiang Ni; et al. (Science China Earth Sciences, 2010)

Gene mapping related to yellow green leaf in a mutant line in rice (Oryza sativa L.) - Peng Du; Ying-Hua Ling; Xian-Chun Sang; Fang-Ming Zhao; Rong Xie; Zheng-Lin Yang; Guang-Hua He (Genes & Genomics, 2009)

Tissue distribution of the secretory protein, SPLUNC1, in the human fetus - Hou-De Zhou; Song-Qin Fan; Jin Zhao; Dong-Hai Huang; Ming Zhou; Hua-Ying Liu; Zhao-Yang Zeng; Yi-Xing Yang; He Huang; Xiao-Ling Li; Shou-Rong Shen; Gui-Yuan Li (Histochemistry and Cell Biology, 2006)